Polymorphism, variation and evolutionary change in early vertebrates from the Gogo Formation, Western Australia - Trinajstic, Kate (Royal Society of Western Australia, 2009)
The imperfection of the fossil record was used by Charles Darwin to explain the lack of evidence for 'organs of extreme perfection and complication', which under his theory of natural selection must have evolved through a series of gradual transitions. In addition, a major premise in the theory of natural selection is that variation between organisms is required so selection for particular traits can occur. The fossil record has subsequently revealed a small number of sites comprising fossils of exceptional preservation including the Gogo Formation of Western Australia. Here a unique Late Devonian (Frasnian) reef fauna, with exceptional three-dimensional preservation of macrofossils combined with unprecedented soft-tissue preservation has preserved examples of the transitional forms and morphological variation Darwin predicted. The most significant discoveries have contributed: insights into reproductive biology, including the oldest known vertebrate embryos and evidence of sexual dimorphism with internal fertilization; the anatomy and variation present in the earliest gnathostomes, the placoderms, provides evidence of directional selection; some of the earliest morphological changes required in the transition from an aquatic to land environment are seen in the primitive tetrapodomorph, Gogonasus.